Improvement of Fracture toughness of soil with ZnO tetrapod. (2018) - Rizvi, Zarghaam Haider; Panda, Shradha; Khan, Mohammad Arsalan; Wuttke, Frank
Abstract: Cracks in clay type soil is a well know problem and has adverse implications in many engineering applications, such as, clay liners, landfill covers, foundations for structures and pavements. Silty clay/ZnO Tetrapod (T-ZnO) nano-geo-composites were prepared with different percentage of T-ZnO between1-5% by weight, by blending the T-ZnO and the soil (direct addition). Fracture toughness of the developed composite is measure through CT test. The results showed that the Tetrapod which has the peculiar shape acts as reinforcement to the clay and silt material offering resistance to deformation and failure. The introduction of the T-ZnO in the soil matrix resulted only in an increase in the fracture toughness of 37% with 1% addition at 17% moisture content, while 30% for the same mixture portion at 19% moisture content. The developed mixture could be applied for clay liners with are susceptible to differential settlement cracks.